Narrativas dialogadas nos diários de campo reflexivos de professoras iniciantes : possibilidades de autoformação - Lorenzzon, Márcia Roza (2017)
This research is attached to the PPGEdu/UFMT/OBEDUC continuing education entitled “Egress of Graduation in Pedagogy and the challenges of practice on the Narrative: The University and the school in an interdisciplinary process of insertion of the beginning teacher on a teaching career”. Such information is offered fortnightly in an itinerant way among the university and six participating schools, starting from a journal indicated by the teachers about what subjects afflict them in the beginning of the teaching career and the need for support and monitoring of a project by the continuing education. The purpose was to follow, to analyze and to comprehend the individualities represented on the narrative writing of the reflective field journals of 4 teachers in continuing formation on the project PPGEdu/UFMT/OBEDUC analyzing how the learning will be interpreted and reassigned by them, and the possible contribution to their professional development. An autobiographical method and the quantitative approach were used and therefore instruments and proceedings of data collect with narratives were connected on the research, such as the reflective field journal and the dialogue narrative interview. The inquiries that helped to move the research were: What do the beginner teachers reveal about the continuing education shared on PPGEdu/UFMT/OBEDUC project? How both formation and the reflexive project starting from the writing and the dialogue on the rereading of the narratives on the reflective field journal contribute to the professional development? Authors were used as a reference to answer those questions, which discuss the beginner teacher, their challenges and difficulties when in the beginning of the career, autobiographical narratives which discuss about the use of reflective field journals in formation use in formative processes. The results indicated on the narratives, that the continuing formation collaborates significantly so as the teachers improve their theoretical and practical knowledge, and the record on the reflective field journals are instruments that they use as a support to their reflections related to the difficulty of the teacher practice in the beginning of the career.